Analisis Hasil Tangkapan Udang Brown (Metapenaeus ensis) di Pelabuhan Perikanan Kuala Pembuang: Analysis of Catching of Brown Shrimp (Metapenaeus ensis) at Kuala Pembuang Fishery Port - Kembarawati, Kembarawati; Gandih, Sweking; Najamuddin, Anang; Rosita, Rosita (Media Ilmiah Teknik Lingkungan (MITL), 2023)
This study aims to determine the results of Catch Per Unit Effort (CPUE), Maximum Sustainable Yield (MSY) and the utilization rate of brown shrimp (Metapenaeus ensis) at the Kuala Pemburan Fishing Port for the last 5 years (2017-2021). The basic method used in this study is a quantitative descriptive method derived from primary and secondary data. Data collection techniques were interviews and primary data collection in the form of shrimp production data at the Kuala Pemburan Fishing Port. Data analysis methods are CPUE, MSY and utilization rate analysis. The results of the study show that the CPUE value has fluctuated from 2017-2021. The highest CPUE value was in 2020 which was 37.76 kg/trip and the lowest was in 2017 which was 8.36 kg/trip. The high and low CPUE values ​​occurred because during this period there was an increase and decrease in both the use of fishing gear and fishing trips. For the yield value (MSY) the optimum fishing effort is 2,940 trips per year and the maximum sustainable catch value is 63,954 kg per year. If viewed based on the sustainable maximum catch value, the number of catches produced in 2020 and 2021 has exceeded the maximum catch limit (Cmsy), but the fishing effort has not exceeded the optimum fishing effort (Emsy). Meanwhile, the yield value of the utilization rate of brown shrimp resources in the last five years indicates that the utilization rate has increased drastically, especially in 2020 and 2021